HOUT-35. RETROSPECTIVE ANALYSIS OF OUTCOMES IN HOSPITALIZED MALIGNANT BRAIN NEOPLASM PATIENTS WITH STATUS EPILEPTICUS. (5th November 2018) - Lobbous, Mina; Gupta, Sahil; Warren, Paula
Abstract: OBJECTIVE: To investigate the key characteristics and outcomes in patients with Malignant Brain Neoplasm and Status Epilepticus. BACKGROUND: Epileptic seizures are a major comorbidity in patients with malignant brain neoplasm (MBN), either at presentation or as a sign of progression. Seizures are more challenging to control in this patient population, especially with rapidly growing tumor and often progress to status epilepticus (SE). We conducted this study to investigate the key characteristics and outcomes in patients with MBN and SE. Methods: Analysis of National Inpatient Sample data (2003–2013) showed a total of 76, 357 patients discharged with a primary diagnosis of MBN, ICD-9 Code 191.X. Among this patient population, 557 patients with SE were identified. We compared age, length of stay (LOS) and total hospital charges between MBN patients with and without SE, as well as the association between MBN and SE with patient race, sex, and disposition status. RESULTS: Analyses revealed that 0.7% of MBN patients were found to have SE. No significant difference was found in age at admission of patients with SE (50.69 vs 51.76 p=0.233). SE was associated with African American (AA) race as compared to non-AA (1.4% vs 0.7%), longer LOS (11.54 vs 6.92 days), higher hospital charges ($113, 416 vs $65, 159), disposition other than home (69.9% vs 44.7%) and increased mortality (15.5% vs 4.1%). CONCLUSION: The results suggest SE is associated with increased morbidity and mortality amongst MBN patients. Our results show an association between SE and increased LOS, worse disposition, higher hospital charges, and mortality. Therefore, early identification and aggressive treatment of SE is warranted in hospitalized patients with Malignant Brain Neoplasm. Future prospective studies are needed to investigate different treatment approaches for Status Epilepticus in hospitalized patients with brain tumors.